2018
DOI: 10.1021/acsami.8b11774
|View full text |Cite
|
Sign up to set email alerts
|

Citrate-Coated, Size-Tunable Octahedral Platinum Nanocrystals: A Novel Route for Advanced Electrocatalysts

Abstract: The development of green and scalable syntheses for the preparation of size-and shape-controlled metal nanocrystals is of high interest in many areas, including catalysis, electrocatalysis, nanomedicine, and electronics. In this work, a new synthetic approach based on the synergistic action of physical parameters and reagents produces size-tunable octahedral Pt nanocrystals, without the use of catalyst-poisoning reagents and/or difficult-to-remove coatings. The synthesis requires sodium citrate, ascorbic acid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 72 publications
2
36
1
1
Order By: Relevance
“…etal nanoparticles (NPs) with different composition, morphology, and surface chemistry can be used for applications like NP-mediated catalysis [1][2][3][4] , cancer therapy [5][6][7] , and chemosensing [8][9][10][11] . To ensure the solubility of pristine metallic NPs in polar solvents, stabilizing agents like citrate and tetraoctylammonium bromide must be introduced into the mixture.…”
mentioning
confidence: 99%
“…etal nanoparticles (NPs) with different composition, morphology, and surface chemistry can be used for applications like NP-mediated catalysis [1][2][3][4] , cancer therapy [5][6][7] , and chemosensing [8][9][10][11] . To ensure the solubility of pristine metallic NPs in polar solvents, stabilizing agents like citrate and tetraoctylammonium bromide must be introduced into the mixture.…”
mentioning
confidence: 99%
“…Besides their high prices, Pt-based catalysts are susceptible to carbonaceous intermediates, especially CO. For example, the CO adsorption on the Pt surface is especially serious in acidic electrolytes, leading to severe poisoning effect or short life time of these catalysts towards MOR. [4][5][6][7] Design and synthesis of high-performance Pt electrocatalyst for MOR (namely maximized catalytic ability towards MOR but minimized CO poisoning effect during MOR) is thus highly demanded.For such a demand, numerous Pt nanostructures (e.g., hollow nanospheres, [8] nanorods or wires, [9,10] nanoclusters, [11] nanoflowers, [12] octahedral, [13,14] nanosponges, and etc. [15] ) have been synthesized using various approaches.…”
mentioning
confidence: 99%
“…For such a demand, numerous Pt nanostructures (e.g., hollow nanospheres, [8] nanorods or wires, [9,10] nanoclusters, [11] nanoflowers, [12] octahedral, [13,14] nanosponges, and etc. [15] ) have been synthesized using various approaches.…”
mentioning
confidence: 99%
“…TEM micrographs mostly show small particle aggregates dispersed into endo/lysosomes, with some single NPs also present (especially for Pd4). Interestingly, analyzing the size of the internalized particles, we observed that PdNPs typically maintain their pristine size after 24 h. This suggests that the particles do not undergo significant dissolution when exposed to the acidic and degradative environment of lysosomes, unlike for instance silver NPs [40,57]. In light of these results, the biocompatibility of PdNPs could be ascribed to the stability of the material (i.e., resistance to the acidic corrosion) in the cellular environment and absence of significant Pd ion release.…”
Section: Toxicity Assessment Of Pdnpsmentioning
confidence: 94%
“…The application of nanomaterials in nanomedicine and nanodiagnostics requires a strict control of their physico-chemical properties, achievable by a careful design of the synthetic procedure [5,7,28,[31][32][33][34][35][36][37][38][39][40]. To this purpose, we developed a new protocol for the synthesis of PdNPs that provides low polydispersity along with size tunability, combined with reagents known to be biocompatible, green, or easy to remove after synthesis.…”
Section: Aqueous Synthesis Of Pdnps and Physico-chemical Characterizamentioning
confidence: 99%